Performance Evaluation Indicators of Space Dynamic Networks under Broadcast Mechanism - Zipeng Ye (American Association for the Advancement of Science (AAAS), 2021)
Large-scale heterogeneous constellations will be the major forms of future space-based systems, and the implementation of numerous derived applications depends mainly on intersatellite communication. The nodes representing heterogeneous satellites will form the networks with rapidly changing topology. However, few researches have been carried out for such networks. This paper studies the broadcast mechanism for space dynamic networks and establishes centralized and distributed routing framework. And then, performance evaluation indicators are proposed to evaluate both the connectivity of dynamic networks and the effectiveness of routing algorithms. Finally, we examine the performance of multigroup networks and verify the rationality of corresponding indicators. We also explore the impact of information survival time which directly affects the delivery ratio and, if unfortunately, may waste the communication resources. Empirical conclusion about the survival time is given in the final part. We believe the performance indicators and the routing algorithms proposed in this paper are great help to future space-based system and both the broadcast mechanism designing.